2013
DOI: 10.1159/000346173
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trend in the Frequency of Ectopic Pregnancies in Lombardy, Italy

Abstract: Background: In recent years, epidemiological data showed that the incidence of ectopic pregnancies (EP) is decreasing, but few data are available on the time trend in Southern European populations. Methods: Using data from the Lombardy Region Database, we calculated and standardized the EP rates/10,000 resident women and the ratios/1,000 pregnancies. Results: Data regarding 1,777,011 pregnancies and 17,028 cases of EP were recorded among women resident in Lombardy between 1996 and 2010, aged 15-50 years old. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Data regarding 1,777,011 pregnancies and 17,028 cases of EP recorded among women resident in Lombardy in a 15-year study period have demonstrated that the proportion of laparoscopic treatment have increased from 25.9% in 1996 to 36.3% in 2010 [60]. …”
Section: Discussionmentioning
confidence: 99%
“…Data regarding 1,777,011 pregnancies and 17,028 cases of EP recorded among women resident in Lombardy in a 15-year study period have demonstrated that the proportion of laparoscopic treatment have increased from 25.9% in 1996 to 36.3% in 2010 [60]. …”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for TOA are similar to those for PID, including multiple sexual partners, prior history of PID, no history of contraceptive use, history of intrauterine device (IUD) insertion, and low socioeconomic status [3]. Long-term complications of PID and TOA are tubal factor infertility, ectopic pregnancy, chronic pelvic pain, and recurrent infection [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…Most ectopic pregnancies are located in the fallopian tube [2]. However, they may also occur in the uterine cervical canal, between the leaves of the broad ligament, within the ovarian cortex, in a scar from a cesarean section or on the peritoneal surface (abdominal pregnancy) [3].…”
Section: Discussionmentioning
confidence: 99%